2017
DOI: 10.1111/resp.13027
|View full text |Cite
|
Sign up to set email alerts
|

Is bronchial thermoplasty cost‐effective as treatment for problematic asthma patients? Singapore's perspective on a global model

Abstract: Background and objective: Bronchial thermoplasty (BT) has been shown to be effective at reducing asthma exacerbations and improving asthma control for patients with severe persistent asthma but it is also expensive. Evidence on its cost-effectiveness is limited and inconclusive. In this study, we aim to evaluate the incremental cost-effectiveness of BT combined with optimized asthma therapy (BT-OAT) relative to OAT for difficult-to-treat and severe asthma patients in Singapore, and to provide a general framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 20 publications
0
22
0
1
Order By: Relevance
“…For example, elevated total serum IgE levels, as well as biomarkers of type 2 inflammation [56], help select patients with severe allergic asthma suitable for anti-IgE therapy with omalizumab and a raised blood eosinophil count identifies patients suitable for therapy with monoclonal antibodies targeting IL-5 with subcutaneous mepolizumab [57], intravenous reslizumab [58] or subcutaneous benralizumab [59]. The GINA guideline considers bronchial thermoplasty as a potential treatment option at step 5 in some countries for selected adults with severe asthma whose asthma remains uncontrolled despite States, bronchial thermoplasty is estimated to be cost-effective in patients with severe uncontrolled asthma who have a high risk of exacerbations [63] or in patients with moderate to severe allergic asthma [64], whereas in Singapore, the procedure is not cost-effective compared to optimized usual care [65]. The likelihood of bronchial thermoplasty being a cost-effective treatment for severe asthma in a health care system are greater if the costs of hospitalization and emergency department are high and the costs of the procedure are low [65].…”
Section: Place Of Bronchial Thermoplasty In the Management Of Severe mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, elevated total serum IgE levels, as well as biomarkers of type 2 inflammation [56], help select patients with severe allergic asthma suitable for anti-IgE therapy with omalizumab and a raised blood eosinophil count identifies patients suitable for therapy with monoclonal antibodies targeting IL-5 with subcutaneous mepolizumab [57], intravenous reslizumab [58] or subcutaneous benralizumab [59]. The GINA guideline considers bronchial thermoplasty as a potential treatment option at step 5 in some countries for selected adults with severe asthma whose asthma remains uncontrolled despite States, bronchial thermoplasty is estimated to be cost-effective in patients with severe uncontrolled asthma who have a high risk of exacerbations [63] or in patients with moderate to severe allergic asthma [64], whereas in Singapore, the procedure is not cost-effective compared to optimized usual care [65]. The likelihood of bronchial thermoplasty being a cost-effective treatment for severe asthma in a health care system are greater if the costs of hospitalization and emergency department are high and the costs of the procedure are low [65].…”
Section: Place Of Bronchial Thermoplasty In the Management Of Severe mentioning
confidence: 99%
“…The GINA guideline considers bronchial thermoplasty as a potential treatment option at step 5 in some countries for selected adults with severe asthma whose asthma remains uncontrolled despite States, bronchial thermoplasty is estimated to be cost-effective in patients with severe uncontrolled asthma who have a high risk of exacerbations [63] or in patients with moderate to severe allergic asthma [64], whereas in Singapore, the procedure is not cost-effective compared to optimized usual care [65]. The likelihood of bronchial thermoplasty being a cost-effective treatment for severe asthma in a health care system are greater if the costs of hospitalization and emergency department are high and the costs of the procedure are low [65]. Other factors that influence the cost-effectiveness of bronchial thermoplasty are a patient's risk of a future exacerbation, the duration of follow-up after treatment and the health systems threshold in dollars for the willingness-to-pay per quality-adjusted life years (QALY).…”
Section: Place Of Bronchial Thermoplasty In the Management Of Severe mentioning
confidence: 99%
“…Zein and colleagues also concluded that BT is a cost effective intervention in patients with asthma at high risk of exacerbations [34]. However, a study carried out in Singapore found that BT is not cost effective compared with optimized asthma therapy unless the cost of the procedure is decreased so as to make it more cost effective [35].…”
Section: Pharmacoeconomics Of Bronchial Thermoplastymentioning
confidence: 99%
“…According to longitudinal administrative data from Singapore, asthma control measured by the Asthma Control Test was associated with higher asthma drug costs, but significantly lower total asthma costs, especially for obese patients . However, in Singapore, the incremental cost‐effectiveness of bronchial thermoplasty combined with optimized asthma therapy was not found superior to optimized asthma therapy alone for difficult‐to‐treat and severe asthma patients …”
Section: Asthmamentioning
confidence: 99%
“…74 However, in Singapore, the incremental cost-effectiveness of bronchial thermoplasty combined with optimized asthma therapy was not found superior to optimized asthma therapy alone for difficult-to-treat and severe asthma patients. 75…”
Section: Costsmentioning
confidence: 99%